Concentration measurement and evaluation of mobility of heavy metals of zayandeh-rood river sediments - Nemati, K.; Bakar, N.K.A.; Abas, M.R.; Sobhanzadeh, E. (2009)
Metallic contaminants associated with sediments showed various behaviours depending on physicochemical conditions. Zayandeh-rood is one of the most important rivers of the centre of Iran. It sources from Zagros Mountains in Charmahal Bakhtiari province and flowing about 350 km, ends to the Gavkhooni marsh in the east of Isfahan. So far, many researches have been conducted to measure the concentration of heavy metals in the environmental samples all over the world and for this purpose, different methods have been proposed. Although several reports have been released concerning the amount of heavy metals concentrations in the air, water or food stuffs, there is less information available about the concentration of heavy metals in the sediments of the rivers and their mobility. The required samples for this research have been taken from 5 different areas: Zaman Khan Bridge, Falavarjan, Vahid Bridge, Ziar and Varzane. Two samples were collected from each of these regions. A five-step sequential extraction procedure, modified from the Tessier method, was applied to the determination of some heavy metals (Cu, Mn, Cd, Ni, Co, Cr, Zn and Pb) in sediment in order to evaluate the potential mobility of fixed metals. The amount of heavy metals were measured utilizing atomic absorption spectrometer (model AA-220, Varian) equipped with graphite oven GTA-110 and the accuracy of part per billion (ppb). A considerable amount of heavy metals exists in the sediments of Zayandeh-rood. These metals and specially manganese, cadmium and nickel have higher poisonous and carcinogenicity effects and mobility. These results therefore help to improve the waste management of such contaminated sediments.